Pengaruh Kompetensi, Motivasi Dan Komitmen Terhadap Efektivitas Kerja Pendamping Program Keluarga Harapan Kabupaten Deli Serdang - Rizka Anggun Fadhillah; S Sugianto; Muhammad Yafiz (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara, 2019)
In this study discusses the influence of competence, motivation and commitment to work effectiveness. The research was conducted at the Social Service, the object of this study was addressed to the Family Program Companion. The population in this study amounted to 122 companions with a total sample of 85 respondents. Then in determining and selecting a research sample using a simple random sampling method. The analytical method used is Partial Least Square. The results showed that competence had a negative effect on the work effectiveness of the Harapan Companion Program. However, motivation and commitment have a significant effect on the work effectiveness of the Harapan Companion Program.